EXPERIMENTAL AND NUMERICAL STUDY OF A VENTURI TUBE AS A DIDACTIC TOOL FOR CHEMICAL ENGINEERING LEARNING - Felipe Orlando da Costa; Jéssica Trindade Martins; Caio Guilherme Sales Ferreira; Giovanna Kellen Tavares de Andrade; Felipe Leonardo Barcelos Mateus; Renata de Aquino Brito Lima Corrêa (The Journal of Engineering and Exact Sciences)
The Venturi tube measures the fluid’s flowrate by use of an obstruction in the flow path. As a tool to understand the fundamental principles of Chemical Engineering, an experimental device for flow measurement integrating a Venturi tube was developed in the course of the Chemical Engineering Projects I from the Federal University of Lavras. The system was constructed with materials of low-cost and easy access. The experimental results for the flow and pressure drop were compared with theorical values and with additional data obtained by the use of a numerical and computational method (CFD). The discharge coefficient was 0.680 ± 0.018 [-], an intermediate value of those found in the literature for orifice plate and flow nozzle meters. The numerical method was successfully able to predict the pressure drop in the system.